The Determination of Some Heavy Metals and Minerals in the Tissues and Organs of the Capoeta umbla Fish Species in Relation to Body Size, Sex, and Age - Canpolat, Ozgur (Foundation Environmental Protection & Research-Fepr, 2013)
In this study, the levels of iron, copper, zinc, (manganese), cobalt, cadmium, lead, chrome, arsenic, mercury, nickel, calcium, and magnesium in the muscle, gill, skin, liver, gonad, and kidney of Capoeta umbla caught from Lake Hazar, Elazig, Turkey were investigated. The concentrations of detected heavy metals were the highest in the liver and the lowest in the muscle. In addition, it has been found that the concentrations of heavy metals and minerals were found to be different in various tissues and organs. The amounts of heavy metals showed differences according to the weight, length, sex, and age groups of the fish. The results were discussed and compared with tolerable values for heavy metals provided by the EPA, WHO, FAO, and Turkish Food Codex to determine whether this species has any risk for human consumption.
Capoeta umbla'nın doku ve organlarında bazı a?ır metallerin ve minerallerin vücut büyüklü?üne, cinsiyete ve yaşa ba?lı de?işimi
Keywords: Accumulation; Capoeta umbla; heavy metal; Lake Hazar; mineral